Roswell delirium [videorecording (DVD)] - Bakewell, Richard; Hall, Anthony Michael; Wallace, Dee, 1948-; MacPhail, Georgia (Gravitas Ventures, 2025)
After the US is hit by a wave of nuclear attacks, a young girl named Mayday receives an intergalactic distress call from space that leads her on a journey of encountering alien visitors, in the hopes they can help save her mother's life.